Review of seafloor spreading around Australia. II. marine magnetic anomaly modelling - Veevers, J. J.; Li, Z. X. (Australian Journal of Earth Sciences, 1991)
This paper updates the models of seafloor spreading magnetic anomalies in the oceanic lithosphere of the Indo-Australian Plate and adjacent plates around Australia. The regions are the eastern Indian Ocean (Argo, Gascoyne, Cuvier and Perth Abyssal Plains), the southeast Indian Ocean (off the southern margin of Australia and the conjugate Wilkes Land margin of Antarctica), the southwest Pacific Ocean (Tasman Sea, Coral Sea and Woodlark Basins) and the Banda Sea, at the southeast edge of the Eurasian Plate. Included in the models for the eastern and southeast Indian Ocean are the magnetic anomaly at the continent-ocean boundary, modelled as the edge-effect of a strongly magnetized oceanic crust abutting a weakly magnetized or deeply buried continental crust. A newly compiled Australian apparent polar wander path (Appendix) provides the values of the remanent-field parameters (inclination and declination) of the magnetic block models. The model dates are confirmed by deep sea (oceanic) drilling. The inception of spreading youngs in a counter-clockwise sense from the Late Jurassic (160 Ma) in the northwest through Early Cretaceous (132.5 Ma) in the west and southwest, Late Cretaceous (96 Ma) in the Southeast Indian Ocean and Tasman Basin, Paleocene (63.5 Ma) in the Coral Sea and Pliocene (3.5 Ma) in the Woodlark Basin.